RELASI BIROKRASI DAN POLITIK DALAM KONTEKS DEMOCRATIC GOVERNANCE - syamsul ma'arif (Universitas Muhammadiyah Lampung, 2021)
The development of Indonesia socio-political situation in the past two decades has encouraged the idea of the need for the government to share roles with non-governmental forces, such as the private sector and the public. Good governance is as a system that allows constructive synergies between the government, the private sector and civil society in the implementation of development. Even the World Bank specifically confirms the important role of good governance in achieving successful development. In this system. the state or government functions to create a conducive political and legal environment, the private sector encourages the creation of employment and community income, while the community itself accommodates social political interaction and participates in various economic, social and political activities. This paper will focus more on the study of efforts to revitalize the government bureaucracy in the midst of configuration changes towards efforts to realize good governance. Keywords: Bureaucracy, Good Governance, Development